Acromegaly and Cushing's syndrome caused by a neuroendocrine tumor arising within a sacrococcygeal teratoma. Issue 11 (14th September 2017) - Babiker, Tarig; Kyrodimou, Efstathia; Berney, Daniel M.; Gurnell, Mark; Drake, William M.; Brooke, Antonia
Key Clinical Message: A 60‐year‐old man with a pre‐existing stable sacrococcygeal teratoma developed acromegaly, ectopic Cushing's syndrome, and 5HIAA secretion. To our knowledge, this represents the first reported case of ACTH and serotonin secretion, and likely GHRH or GH cosecretion, from a sacrococcygeal teratoma in an adult. Abstract : A 60‐year‐old man with a pre‐existing stable sacrococcygeal teratoma developed acromegaly, ectopic Cushing's syndrome, and 5HIAA secretion. To our knowledge, this represents the first reported case of ACTH and serotonin secretion, and likely GHRH or GH cosecretion, from a sacrococcygeal teratoma in an adult.